Preparation of Flower-like Nanosilver Based on Bioderived Caffeic Acid for Raman Enhancement and Dye Degradation - Xing, Lili (Langmuir : the ACS journal of surfaces and colloids, 2024)
In this study, a simple, green, and low-cost room temperature synthesis of broccoli-like silver nanoflowers (AgNF) with a particle size of about 300-500 nm was developed using plant-derived caffeic acid as a reducing agent and polyvinylpyrrolidone as a dispersant under ultrasound assistance. The flower clusters covered by small nanocrystals of 20-50 nm significantly enhance the electromagnetic field signals. AgNF was deposited on the surface of silicon wafers as a surface-enhanced Raman spectroscopy sensor for the detection of probe molecules such as rhodamine 6G (R6G) and malachite green with high sensitivity, homogeneity, and reproducibility. AgNF was deposited on cotton fabrics in the form of composites to catalyze the degradation of dye pollutants such as R6G, MG, and methyl orange in the presence of sodium borohydride. 0.1 g of AgNF/cotton fabric could assist 15 mmol/L NaBH4 to achieve over 90% degradation of various dyes as well as a high concentration of dyes in 12 min with good reusability and recyclability. The AgNF synthesized in this work can not only monitor the type and amounts of pollutants (dyes) in wastewater but also catalyze the rapid degradation of dyes, which is expected to be valuable for industrial applications